1987
DOI: 10.1161/01.cir.76.6.1353
|View full text |Cite
|
Sign up to set email alerts
|

Laser probe ablation of normal and atherosclerotic human aorta in vitro: a first thermographic and histologic analysis.

Abstract: The metal-tipped optical fiber or "laser probe" has been extensively studied in animal preparations in vivo and in human clinical trials of revascularization. The aim of this study was to evaluate the thermal characteristics of laser probe tissue ablation and to contrast the vascular tissue response to exposure to the laser probe and bare optical fiber. A 2 mm laser probe was heated with up to 4 W of argon-ion laser irradiation and applied to six postmortem strips ofhuman nonatherosclerotic aorta as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Recent elegant in vitro thermographic studies of normal and diseased human aorta do provide some insight into the mechanism of action of one laser recanalization device, the laser probe. 10 In this study, it was found that the laser thermal probe was more effective in ablating fibrofatty plaque than nonatherosclerotic aorta. It was postulated that lower thermal conductivity and difflsivity constants of fibrofatty plaque relative to normal vessel wall were responsible for more extensive heating and evaporation of plaque.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent elegant in vitro thermographic studies of normal and diseased human aorta do provide some insight into the mechanism of action of one laser recanalization device, the laser probe. 10 In this study, it was found that the laser thermal probe was more effective in ablating fibrofatty plaque than nonatherosclerotic aorta. It was postulated that lower thermal conductivity and difflsivity constants of fibrofatty plaque relative to normal vessel wall were responsible for more extensive heating and evaporation of plaque.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 76%
“…10 The authors postulate on the basis of their histological observations that compression of residual cellular and tissue components results in a decrease in the vacuolated cellular space. Thus, heat and pressure appear to be two important mechanisms of the "contact" laser approach to atherosclerotic lesions.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…The results reported here suggest that laser probe temperatures of this level can be attained in blood but not in saline (using argon laser energy and aluminum tipped fibers). Other investigators have reported higher energy requirements for plaque ablation in saline [13,19,20], and Welch et al [21] have reported that lower laser probe temperatures are achieved in water than in blood for the same amount of energy input. This apparent decreased efficiency of probe heat generation and thermal ablation in saline can possibly be explained by the fact that saline will remain at 100°C until water is vaporized [3,22].…”
Section: Discussionmentioning
confidence: 97%
“…The characteristics of this device are determined by its surface temperature. There are many parameters which may influence this temperature such as : input power, probe mass, exposure time, environment, contact xvith tissue, probe motion and flow (20,21).…”
Section: Thernml Properties Metal Laser Probementioning
confidence: 99%
“…Despite the large number of patients treated in peripheral vessels, the working mechanism of the metal laser probe is not well understood (20,21). In order to measure the temperature of the probe a thermocouple was installed in a coaxial channel.…”
Section: Thermal Properties Metal Laser Probementioning
confidence: 99%